NETWORK FEATURES STUDY OF THE COMMUNICATION INTERFACE OF MULTIPROCESSOR MODULAR SYSTEMS (Computer systems and information technologies, 2022)
This paper considers so-called “blade” server solutions of multiprocessor systems with several of the same type of maternal modules installed in a single case. It is shown that the computations parallelisms effectiveness of such systems significantly depends on many factors; one of the most essential is the data features between the neighboring nodes of the multiprocessor system, which is usually the slowest part of the algorithm and can negate the effect of the number of used processors. The network interface channel aggregation can solve the indicated problem.The studies show that, at present, the channel aggregation problem in modular multiprocessor cluster systems has not been solved properly. Meantime, there are critically few studies that reveal the architectural influence of the multiprocessor system network interface on computing performance.The work set the goal to improve the network interface structure of the multiprocessor system and increase its performance by multidimensional network interface channels aggregation, adapted to solving the studied class problems. At the same time, the network interfaces main operating modes in multiprocessor computing systems were analyzed, their impact on the assessment of the parallelization performance was revealed, and ways to increase the multiprocessor system efficiency by its network interface architecture reorganization.An analysis of the detected modes of network interface operating in the modular multiprocessor cluster system was run. For the first time, analytical ratios of the multiprocessor computing system efficiency were derived from its network interface parameters. The operation conditions of the cut-through switch are determined so that the information is transmitted without the store-and-forward switching procedure. That approach ensures the transmission of the package at the highest speed, which leads to improving the multi-processing system efficiency in the organization of multi-channel modes of its network interface operation.The practical value of the results obtained is the proposed multiprocessor system application to create new technological processes. Separately, the application relevance of the proposed approach to solve the digital economy problems should be noted.  Keywords: multiprocessor systems, network interface, aggregation, computing nodes, acceleration of computations.Статтю присвячено дослідженню так званих "блейд" серверних рішень багатопроцесорних обчислювальних систем, відповідно до яких декілька однотипних материнських модулів встановлюються в одному корпусі. Показано, що ефективність розпаралелювання обчислень таких систем істотно  залежить від багатьох чинників. Проте, один з найважливіших - це особливості пересилки даних між сусідніми вузлами багатопроцесорної системи, яка зазвичай є найповільнішою частиною алгоритму. У зв'язку з цим підкреслюється, що важливим чинником підвищення ефективності функціонування модульних багатопроцесорних систем є проблема вибору, конструювання і організації їх мережевих інтерфейсів.Відзначається, що вказану проблему можна розв'язати за рахунок агрегації каналів мережевого інтерфейсу. Проте нині проблема агрегації каналів в модульних багатопроцесорних кластерних системах не розв'язана належним чином. З іншого боку, критично мало досліджень, в яких розкривався би вплив архітектури мережевого інтерфейсу багатопроцесорної системи на ефективність розпаралелювання обчислень. У роботі поставлена мета  удосконалення структури мережевого інтерфейсу багатопроцесорної системи та підвищення її продуктивності за рахунок багатовимірної агрегації каналів мережевого інтерфейсу, адаптованого до розв’язування задач досліджуваного класу. При цьому проведено аналіз основних режимів роботи мережевого інтерфейсу у багатопроцесорних обчислювальних системах і виявлено їх вплив на оцінки ефективності розпаралелювання, а також показано шляхи підвищення ефективності багатопроцесорної системи за рахунок реорганізації архітектури її мережевого інтерфейсу. Уперше виведені аналітичні співвідношення оцінок ефективності багатопроцесорної обчислювальної системи через параметри її мережевого інтерфейсу. Проведений аналіз виявлених режимів роботи мережевого інтерфейсу в модульній багатопроцесорній кластерній системі.  Визначені умови роботи комутаційної матриці комутатора в  режимі наскрізної  комутації (cut - through) з тим, щоб інформація передавалася без використання процедури буферизації. Такий підхід забезпечує передачу пакетів з найбільшою швидкістю, що призводить до поліпшення оцінок ефективності багатопроцесорної системи при організації багатоканальних режимів функціонування її мережевого інтерфейсу. Практична цінність отриманих результатів полягає в застосуванні запропонованої багатопроцесорної системи для створення нових технологічних процесів. Окремо слід зазначити актуальність застосування запропонованого підходу для розв’язування задач цифрової економіки. Ключові слова: багатопроцесорні системи, мережевий інтерфейс, агрегація, обчислювальні вузли, прискорення обчислень.
Keywords: multiprocessor systems; network interface; aggregation; computing nodes; acceleration of computations